Exotic or not, leaf trait dissimilarity modulates the effect of dominant species on mixed litter decomposition - Finerty, G; de Bello, F; Bílá, K; Berg, M; Dias, A; Pezzatti, G; Moretti, M (Wiley, 2016)
1.It has long been recognized that leaf traits exert a crucial control on litter decomposition, a key process for nutrient cycling, and that invading species can greatly alter such soil processes via changes in mixed litter trait composition. Trait effects on ecosystem processes are hypothesized to operate via changes in either dominant trait values in the community (often calculated as community weighted mean trait values; CWM) or trait functional diversity (dissimilarity between species trait values; FD). Few have studied the effects of these community trait components in tandem due to their interdependence. 2.We studied litter mixture decomposition using three exotic and six native European tree species with a range in litter decomposability, to disentangle the unique and combined roles of CWM and FD in explaining net litter mixture mass loss. 3.We showed that while CWM exerted the strongest effect on mass loss, FD modulated its effects, increasing mass loss in mixtures with low mean decomposability and decreasing mass loss in mixtures with high mean decomposability. Litter species identity and native/exotic status explained relatively little additional variation in mass loss after accounting for CWM and FD. We further showed that alterations to CWM and FD were more important than the replacement of a native species with an exotic counterpart in predicting mass loss. 4.Synthesis:Our results indicate that the effect of adding an exotic or losing a native species on litter decomposition rate can be predicted from how a species alters both CWM and FD trait values. This supports the idea that the repercussions of exotic species on ecosystem processes depends on the extent that introduced species bear novel traits or trait values and so on how functionally dissimilar a species is compared to the existing species in the community.